Variations in stroboscopic patterns in perceptually phononormic individuals - N, Sreedevi; Pebbili, Gopi Kishore; TK, Prakash; Bharadwaj, Shishira. S (Journal of All India Institute of Speech and Hearing)
The present study was intended to examine the stroboscopic parameters with regard to the extent and type of deviancies or variations from normalcy in perceptually phononormic individuals. Fifty perceptually phononormic individuals who served as the participants for the study were made to undergo Videostroboscopic examinations by an experienced Otolaryngologist. Later, all the recordings were examined, and under glottal activity majority of the parameters inclined towards normalcy but for certain deviations noticed for glottis closure and amplitude. Under supraglottal activity variations were noticed mainly under the structure and functioning of epiglottis, ventricular folds and arytenoids. These ndings of the current study advocate that the presence of slight anatomically deviant parameters (probable normal variations) alone without any related presenting complaints do not serve as diagnostic hallmarks, mainly in cases of Functional or Non organic dysphonia and serves to caution in exercising just the theoretical framework in diagnosis of primarily functional dysphonia.